Inclusive Education is a Multi-Faceted Concept - David Mitchell (Center for Educational Policy Studies Journal)
With the impetus of the UN Convention on the Rights of People with  disabilities, inclusive education is an idea whose time has arrived around the world. Its scope goes far beyond learners with disabilities and has now been extended to cover all learners with special educational needs, whatever their origins. It also extends beyond the mere placement of such learners in regular classes to include consideration of multiple facets of education. The present paper examines a model of inclusive education that, in addition to placement, embraces vision, curriculum, assessment, teaching, acceptance, access, support, resources and leadership. For each of these facets, criteria are specified and indicators are suggested.